COVID-19: sleep research perspectives - Najafi, Arezu; Sadeghniiat-Haghighi, Khosro; Alemohammad, Zahra Banafsheh; Akbarpour, Samaneh (Sleep Science, 2020)
Coronavirus disease of 2019 (COVID-19) pandemic originated from Wuhan in December 2019 and has been spread in whole China and the world. Worldwide outbreaks of COVID-19 triggered a large number of morbidities and mortalities beside its economic and social burdens, which are discussed a lot, in scientific literature and different types of media. As a sleep medicine specialist, we may wonder how we can be involved in this field. In this short theoretical essay, we will discuss about the known facts as well as the hypotheses, which associate the sleep medicine to COVID-19. The discussed points may provide a source of research ideas throughout the world for better understanding of novel coronavirus-19 that has devastating effects on humanity.
Keywords: Sleep; Coronavirus Infections; Research